2002
DOI: 10.1034/j.1600-0560.2002.291004.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the histiocytic marker PG‐M1 in granuloma annulare and rheumatoid nodules of the skin

Abstract: PG-M1 is consistently and strongly expressed by the histiocytic population of GA and RN, being more sensitive and reliable than other histiocytic markers. We recommend its use in difficult cases in which the histiocytic nature of the lesion needs to be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
2
11
1
Order By: Relevance
“…This is in accordance with a recent report showing KP-1 staining in 86% of GA. 12 It is in contrast to one previous report, in which the histiocytic infiltrate fails to stain for KP1 and HAM56. 11 The current study, similar to the study by Groisman et al, 12 used antigen retrieval on formalin-fixed, paraffinembedded sections, whereas antigen retrieval was not used in the earlier study. 11 This may explain the differences in the results.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This is in accordance with a recent report showing KP-1 staining in 86% of GA. 12 It is in contrast to one previous report, in which the histiocytic infiltrate fails to stain for KP1 and HAM56. 11 The current study, similar to the study by Groisman et al, 12 used antigen retrieval on formalin-fixed, paraffinembedded sections, whereas antigen retrieval was not used in the earlier study. 11 This may explain the differences in the results.…”
Section: Discussioncontrasting
confidence: 72%
“…Immunohistochemical studies on the histiocytic and lymphocytic components have generated variable results. [11][12][13][14][15] Mycosis fungoides (MF), a form of cutaneous T-cell lymphoma, most often presents as a papulosquamous eruption involving the lower trunk, buttocks, hips, breasts (in women), and axillae (so called ''bathing trunk'' distribution). Histologically, diagnostic changes of MF include a superficial, patchy lichenoid infiltrate of cytologically atypical lymphocytes trafficking in the epidermis (epidermotropism).…”
mentioning
confidence: 99%
“…Zelger et al 7 , however, stressed that all 15 cases of cellular neurothekeomas studied showed positive reactions for KiM1p, which is a useful pan‐monocyte marker. Nevertheless, positivity for KP‐1 in cellular neurothekeoma such as in this case is exceptional, 15 and it is notable that this case diffusely expressed PG‐M1, which shows more restricted reactivity with elements of monocyte/macrophage lineage than previously described histiocytic markers (MAC‐37, KP1 and Ki‐M1p), and is the most reliable histiocytic marker 16–18 . This cellular neurothekeoma, expressing both KP‐1 and PG‐M1, is considered to show true histiocytic differentiation, and could be explained by one of the following three interpretations.…”
Section: Discussionmentioning
confidence: 49%
“…Nevertheless, positivity for KP-1 in cellular neurothekeoma such as in this case is exceptional, 15 and it is notable that this case diffusely expressed PG-M1, which shows more restricted reactivity with elements of monocyte/macrophage lineage than previously described histiocytic markers (MAC-37, KP1 and Ki-M1p), and is the most reliable histiocytic marker. [16][17][18] This cellular neurothekeoma, expressing both KP-1 and PG-M1, is considered to show true histiocytic differentiation, and could be explained by one of the following three interpretations. The first interpretation is that cellular neurothekeomas, including our case, are actually plexiform and epithelioid variants of dermatofibroma, as suggested by Zelger et al 7 , who pointed out the relationship between cellular neurothekeoma and dermatofibroma based on consistent reactivity with Ki-M1p and a variable immunohistochemical profile (factor XIIIa, smooth muscle-specific actin, antimetallothinein, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral rim of histiocytes may form a palisaded pattern (Fig. 422,423 The intervening areas of the dermis between the necrobiotic granulomas are relatively normal compared with necrobiosis lipoidica, and there is no fibrosis. Variable numbers of multinucleate giant cells are found in this zone.…”
Section: Histopathologymentioning
confidence: 99%